Neural networks during delay discounting as trans-disease marker: A meta-analytical review. (July 2021) - Chen, Zhiyi; Becker, Benjamin; Qin, Pengmin; Lei, Wei; Chen, Jing; Liu, Peiwei; Lin, Tian; Zhang, Chenyan; Zhang, Rong; Wang, Mengmeng; Xu, Ting; Yang, Yaqi; et al.
Abstract: Delay discounting reflects a devaluation of delayed long-term benefits but pursuing immediate rewards. Higher discounting rates (h-DR) are found ubiquitous in many diseases and unhealthy conditions, particularly in addiction disorder (AD), attention-deficit/hyperactivity disorder (ADHD), and obesity. Thus, h-DR was considered to be a common benchmark across many diseases facilitating to understand one disease to relevant others, which was called trans-disease process. However, the common and specific neural biomarkers associated with this process has not yet been studied well. We performed a voxel-wise task-related neuroimaging meta-analysis to clarify the neural pattern of trans-disease process across AD, ADHD and obesity. We recruited 19 eligible papers, including 9 AD papers (154 patients), 6 ADHD papers (106 patients) and 4 obesity studies (94 patients). Neuroimaging meta-analysis demonstrated the presence of neural biomarkers of trans-disease process: these patients showed inadequate brain response in caudate, ventromedial and dorsolateral prefrontal cortex (dlPFC) than do of healthy controls (HCs). Disease-specific neural patterns were also found, with prominent hypoactivation in parahippocampal-striatum network for AD, hyperactivation in dopamine-projection striatum network for ADHD and decreased activity in dorsal anterior cingulate cortex and dlPFC for obesity. This study provided robust evidence to reveal the neural substrates of trans-disease process, as well further promoted the triple brain network model in favor of the theoretical developments of these neuropsychiatric disorders.